Financial Performance Analysis and Investment Efficiency among Hotels in Kendari - Riski Andriana Putri; Sitti Zakiah; Fajar Saranani (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study explores how financial performance, managerial discipline, investment efficiency, and hotel performance are related among the hotels in Kendari, Southeast Sulawesi. The quantitative method was adopted where 200 hotel managers and employees complete structured questionnaires and then analysed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings indicate that financial performance and managerial discipline have a significant and positive effect on investment efficiency that consequently affect the hotel performance. The efficiency of investment is an intermediate variable between financial and managerial variables and performance. The results confirm agency and efficiency theories, meaning that financial stability and disciplined management increase capital use and performance in general. The research is relevant to the literature of hospitality finance and offers practical advice on how to enhance managerial governance and sustainable competitiveness in the functioning of the regional hotel business.